2021
DOI: 10.3389/fpsyg.2021.710517
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Working From Home During the COVID-19 Crisis and HR Practitioner Response

Abstract: The pandemic has changed the way people work, and more and more people are choosing to work from home (WFH). Unlike traditional work patterns, this approach has limitations and has had a significant impact on both organizations and individuals. It also brings many challenges to the work of HR practitioners. HR practitioners, as key players in strategic human resource management, need to take advantage of management innovations under the crisis to improve employees’ work flexibility and effectively address the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(100 citation statements)
references
References 38 publications
0
44
0
Order By: Relevance
“…Creating an enabling work environment, monitoring and reinforcing acceptable behaviour, and optimizing process organization and burden are all things that may be done. (28)…”
Section: Methodsmentioning
confidence: 99%
“…Creating an enabling work environment, monitoring and reinforcing acceptable behaviour, and optimizing process organization and burden are all things that may be done. (28)…”
Section: Methodsmentioning
confidence: 99%
“…They cite, for example, the need for commuting, time flexibility, or, for example, focusing on work as the best-rated benefits [2]. Chen [18] also mentions many identical advantages and disadvantages of working from home during the Covid-19 pandemic in their study of the impact of working from home on employees. Based on other expert studies and surveys, Chen [18] concluded that, among other things, insufficient skills of employees, uncertainty about redundancies, wage cuts, and bankruptcies are some of the significant negatives of working from home for employees.…”
Section: Literary Researchmentioning
confidence: 99%
“…Chen [18] also mentions many identical advantages and disadvantages of working from home during the Covid-19 pandemic in their study of the impact of working from home on employees. Based on other expert studies and surveys, Chen [18] concluded that, among other things, insufficient skills of employees, uncertainty about redundancies, wage cuts, and bankruptcies are some of the significant negatives of working from home for employees. For managers, for example, it is the inability to thoroughly control and supervise subordinates or the lack of interaction with them [18].…”
Section: Literary Researchmentioning
confidence: 99%
“…Unprecedentedly, the rate of employees working from home in Europe during the pandemic has increased to 48%, moreover, approximately half of them were without any previous teleworking experience (Eurofound, 2020 ). This change was rapid and without proper preparation on behalf of both, the organisations and their employees (Chen, 2021 ). For example, due to the sudden nature of this transition, less than half of the employees reported having been provided with the equipment needed to work from home by their employers (Eurofound, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, most employees received only limited or no support from their organisations. They had to rely on their own resources while dealing with newly emerged challenges to manage work and home interfaces (Chen, 2021 ). Thus, the importance of various individual skills that help manage home and work interfaces has only increased.…”
Section: Introductionmentioning
confidence: 99%